53 Health Outcomes of Siblings of Children with Chronic Health Conditions: A Systematic Review and Meta-Analysis. (29th October 2021) - Martinez, Benjamin; Pechlivanoglou, Petros; Meng, Dorisa; Traubici, Benjamin; Mahood, Quenby; Korczak, Daphne; Colasanto, Marlena; Mahant, Sanjay; Orkin, Julia; Cohen, Eyal
Abstract: Primary Subject area: Mental Health Background: Chronic childhood health conditions are known to have an impact on the well-being of family members. Parental caregivers face well-defined adverse health outcomes, though less is known about the health impacts on siblings. Objectives: To assess clinical health outcomes in siblings of children with chronic health condition(s) compared to siblings of healthy children or normative data. Design/Methods: We searched Ovid MEDLINE, EMBASE, the Cochrane Central Register of Controlled Trials, PsycInfo, and CINAHL through June 4, 2020. We included English-language studies that: (1) reported clinically diagnosable mental or physical health outcomes of siblings of children (0-18 years old) diagnosed with any childhood chronic health condition; (2) included a comparison group; and (3) used an experimental or observational study design. Risk of bias was assessed using the Newcastle-Ottawa Scale. Results: We included 28 studies of the 9053 screened, comprising 10 cohort studies and 18 cross-sectional studies. Studies from 11 different countries reported most commonly on siblings of children with disabilities (12 studies), cancer (8 studies), or psychiatric disorders (4 studies). Siblings of children with chronic conditions had greater depression rating scale scores than their comparison groups (standardized mean difference 0.49; 95% CI 0.33-0.65; P < .001 [5 studies]) (Fig. 1), whereas anxiety scores did not differ significantly (standardized mean difference 0.24; 95% CI -0.03-0.52; P = .08 [6 studies]) (Fig. 2). Studies that reported on prevalence of psychiatric diagnoses, rather than rating scale scores, had mixed results, either indicating increased risk (3 studies) or no increased risk (4 studies) among exposed siblings. We did not meta-analyze effects for mortality (3 studies) or physical health outcomes (dental caries [1 study], traumatic brain injury [1 study], sexually transmitted infection [1 study], overweightness/obesity [1 study]) given the limited number of studies and between-study heterogeneity. Included studies were rated as high quality (12 studies) or of moderate quality (16 studies). Conclusion: Siblings of children with chronic health conditions may be at an increased risk of depression. Our findings suggest the need for targeted interventions to support the psychological well-being of siblings of children with chronic health conditions.